A Comparison of the Catherine Bergego Scale and the Semi-Structured Scales for Functional Evaluation of Hemi-Inattention in patients with stroke - Vorster, Kara (My University, 2022)
Background It is common to experience unilateral neglect after suffering from a stroke. This can have an effect on the patient’s activities of daily living, the rehabilitation process and the length of stay in hospital. There are many different outcome measures that can be used to measure unilateral neglect. It is therefore important to determine which outcome measure is best used in a South African in-patient rehabilitation hospital. The aim of this study was to compare the responsiveness of the CBS via the KF-NAP to the Two Semi-Structured Scales for Functional Evaluation of Hemi-inattention when measuring unilateral neglect in adult patients following a stroke in a neurological rehabilitation unit. Method Forty-one patients from Witrand Hospital Rehabilitation unit were recruited to participate in this study. All of the participants included in this study experienced a first-ever stroke and they were excluded if they had severe speech impairments, were confused or had impairments or activity limitations that are not related to stroke. All participants gave informed consent and thereafter the Catherine Bergego Scale (CBS) and the Two Semi-Structured Scales for Functional Evaluation of Hemi-inattention was then administered. The scores were calculated for the CBS & the Two Semi-Structured Scales for Functional Evaluation of Hemi-inattention by adding the results of each item for each patient. The different categories were also scored individually. Frequencies and percentages for the CBS via KFNAP and the Two Semi-Structured Scales for Functional Evaluation of Hemi-inattention were calculated. Results It was determined that the majority of study participants experienced neglect on admission at the Rehabilitation unit. The unilateral neglect mean score during admission was higher than the score on discharge with the CBS and the Two Semi-Structured Scales for Functional Evaluation of Hemi-inattention. The p-value comparing mean scores of the two methods, was 0,308 which showed that statistically there was no difference when comparing the two outcome measures. Conclusion This study found that either the CBS via the KF-NAP or the Two Semi-Structured Scales for Functional Evaluation of Hemi-inattention are responsive when measuring unilateral neglect in a rehabilitation setting.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Physiotherapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022